2001
DOI: 10.1080/01443610120059897
|View full text |Cite
|
Sign up to set email alerts
|

Grandmultiparitytrends and complications: a study in two hospital settings

Abstract: Pregnancy after the fifth delivery is viewed with anxiety, especially by obstetricians in developing countries working with inadequate facilities. High parity is still common with serious consequences to the fetus, the mother, the family and society. In the last 40 years, non-governmental, national and international efforts have been made to reduce fertility rates. We therefore intended to determine the trend in the grandmultiparity rates from 1 January 1987 to 31 December 1994 in the South Western part of Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…The spontaneous vaginal delivery rate was within the range of 55.35% to 95.2%, which was similar to earlier reports from other centres in Nigeria [1,4,19].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The spontaneous vaginal delivery rate was within the range of 55.35% to 95.2%, which was similar to earlier reports from other centres in Nigeria [1,4,19].…”
Section: Discussionsupporting
confidence: 90%
“…Majority of the patients delivered at term and the incidence of post term was higher than that reported from South Africa [14]. Macrosomic babies accounted for 16% of birth weights while low birth weight rate was similar to findings in Ibadan [4]. The significant low birth weight could be from high incidence of twin pregnancy, premature rupture of membrane, preterm labour, intrauterine growth restriction which could occur in patients with hypertensive disorders as well as iatrogenic prematurity from delivery of patients with severe preeclampsia.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Hence, high parity is not considered to be a risk factor for pregnancy-related complications [7-9]. Conversely, a high prevalence of GM has been reported in “developing” countries [10-12]. …”
Section: Introductionmentioning
confidence: 99%
“…Caesarean section rates increased with increasing parity in our study (p <0.001). A Nigerian study found increased caesarean section rates for grand multiparous women 34 . Women who booked for antenatal care were less likely to have a caesarean section in this study (p = 0.0018).…”
Section: Discussionmentioning
confidence: 99%